Efektivitas Penggunaan Media Kartu Bergambar Untuk Pembelajaran Mufradat Di MI - Riski Gunawan; Okta Novianti; Mohammad Zainal Hamdy (Sekolah Tinggi Agama Islam Syaichona Moh. Cholil Bangkalan, 2022)
This study aims to determine the effectiveness of using picture card media for mufradat learning at MI Al-Istiqomah Banjit Way Kanan after the development and validation process of the product. Researchers are interested in developing this media because mufradat learning at MI is still using conventional media, so there is a need for media that can assist in mufradat learning at MI Al-Istiqomah Banjit Way Kanan. This study uses the type of research and development (Research and Development) or R&D, namely the research method used to produce a particular product and test the feasibility of the product. Using the ADDIE model developed by Dick and Carry, it is arranged programmatically with systematic sequences of activities in an effort to solve learning problems related to learning resources, needs and learning characteristics. This model consists of five steps, namely: Analysis (analyze), Design (design), Development (development), Implementation (implementation) and Evaluation (evaluation). However, in this study, the researchers only discussed the effectiveness of using picture card media after the expert validation process and product testing. The research instrument used was a questionnaire. While the data analysis technique used is descriptive data analysis technique, namely by describing the effectiveness of using picture card media in mufradat learning. Based on the results of data analysis, after going through the process of product validation and testing and responses from student questionnaires, 80% were in the very effective category. So it can be concluded that the media is feasible, effective and can be used as a supporting medium for learning Arabic, especially mufradat.